A Case of Postoperative Hematoma Mimicking Giant Hydrocele - Qamer, Maham; Qureshi, Abid; J Etwaru, Dhanan (Journal of Clinical Case Reports and Images, 2025)
Background In adult males, non-communicating hydroceles are non fluctuant scrotal swellings that are formed when there is an imbalance of fluid secretion and absorption between the parietal and visceral layers of the tunica vaginalis. Giant hydroceles are a rare manifestation and have previously been classified as hydroceles that drain more than 1000 mL of fluid. In this report, we describe a case of a giant hydrocele requiring surgical management and highlight a review of the literature. Case Presentation A 34-year-old male presented with complaints of large right-sided scrotal swelling, accompanied by scrotal discomfort. Ultrasound of the right testicle revealed a large hypoechoic space with a complex collection and posterior displacement of the testicle, indicating a possible hydrocele. The patient was taken to the operating room for a right hydrocelectomy. Approximately 2 liters of fluid were drained from the sac.  Discussion Hydroceles are defined as straw-colored fluid collections within the parietal and visceral layers of the tunica vaginalis. Giant hydroceles, defined as fluid collections within the tunica vaginalis exceeding 1000 mL, are rare and the management of such cases is sparsely documented in the literature. While most asymptomatic fluid collections resolve spontaneously, larger collections with inflammatory changes within the testicular wall may require surgical intervention, either laparoscopic or open.
Keywords: giant hydrocele; hydrocelectomy; scrotal swelling; hematoma